2005
DOI: 10.1523/jneurosci.4940-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Stimulated Adenylyl Cyclases Modulate Ethanol-Induced Neurodegeneration in the Neonatal Brain

Abstract: Fetal alcohol exposure results in cognitive and neurobehavioral deficits, but the effects of modifying genetic loci on the severity of these sequelas have not been well characterized. Although the cAMP signaling pathway has been shown to be an important modulator of ethanol sensitivity in adult mice, its potential role in modulating ethanol-induced neurodegeneration has not been examined. Adenylyl cyclases (ACs) 1 and 8 produce cAMP in response to intracellular calcium elevation and modulate several aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
(63 reference statements)
4
27
0
Order By: Relevance
“…Further, neurons sensitive to agents such as MK801 or nimodipine may be generally sensitive to agents or events that alter intracellular calcium, reflecting an inability to buffer changes in calcium at P7 (but not at later ages) that makes these neurons selectively vulnerable. That reduction in intracellular calcium plays some role in mediating the age-dependent toxicities we describe here is supported by evidence showing calcium-sensitive adenylate cyclases are downstream targets following NM-DAR blockade [Maas et al, 2005]. Further, recent observations in our lab indicate that MK801-induced activated caspase-3-ir is inversely related to expression of calcium binding proteins [Lema Tome et al, in press].…”
Section: Widespread Brain Injury Following Calcium Channel Blockadesupporting
confidence: 80%
“…Further, neurons sensitive to agents such as MK801 or nimodipine may be generally sensitive to agents or events that alter intracellular calcium, reflecting an inability to buffer changes in calcium at P7 (but not at later ages) that makes these neurons selectively vulnerable. That reduction in intracellular calcium plays some role in mediating the age-dependent toxicities we describe here is supported by evidence showing calcium-sensitive adenylate cyclases are downstream targets following NM-DAR blockade [Maas et al, 2005]. Further, recent observations in our lab indicate that MK801-induced activated caspase-3-ir is inversely related to expression of calcium binding proteins [Lema Tome et al, in press].…”
Section: Widespread Brain Injury Following Calcium Channel Blockadesupporting
confidence: 80%
“…We have chosen these isoforms of AC because our preliminary study identified AC6, -7, and -8 as the major isoforms of AC in the hypothalamic cells that are ethanol-sensitive (Yoshimura and Tabakoff, 1999;Chandler et al, 2004;Maas et al, 2005). We have also determined the effect of the cAMP analog dbcAMP on ethanol-induced alterations in the number of ␤-EP neurons and TUNEL-positive ␤-EP neurons in hypothalamic cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…VINP treatment is likely to increase cAMP signaling, which in turn would enhance the activity of a large number of factors downstream from the NMDA receptor, any of which may be downregulated in FAS. In fact, it has been suggested that an alteration in the cAMP cascade may play an important role in the deleterious effects of early alcohol exposure on brain development (Maas et al, 2005). A possible explanation for an alteration of cAMP levels after early alcohol exposure is related to the upregulation of calmodulin (CaM) that has been demonstrated to occur after chronic alcohol exposure (Pant et al, 1985;Hamoudi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%